2021
DOI: 10.1038/s41598-021-97859-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 1 expression is higher in muscle of old vs. young males, and increases upon resistance exercise in older adults

Abstract: Aged skeletal muscle undergoes metabolic and structural alterations eventually resulting in a loss of muscle strength and mass, i.e. age-related sarcopenia. Therefore, novel targets for muscle growth purposes in elderly are needed. Here, we explored the role of the cannabinoid system in muscle plasticity through the expression of muscle cannabinoid receptors (CBs) in young and old humans. The CB1 expression was higher (+ 25%; p = 0.04) in muscle of old (≥ 65 years) vs. young adults (20–27 years), whereas CB2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…Another limiting factor may have been the different ages of the mice used in the short-term and long-term treatment experiments ( Willinghamm et al, 2010 ; Daroszewska et al, 2018 ). In the older animals, our results could be explained by low CB2 receptor expression, as the number of cannabinoid receptors on bone cells might also be altered at older ages, as has been shown for skeletal muscle ( Dalle and Koppo, 2021 ).…”
Section: Discussionsupporting
confidence: 54%
“…Another limiting factor may have been the different ages of the mice used in the short-term and long-term treatment experiments ( Willinghamm et al, 2010 ; Daroszewska et al, 2018 ). In the older animals, our results could be explained by low CB2 receptor expression, as the number of cannabinoid receptors on bone cells might also be altered at older ages, as has been shown for skeletal muscle ( Dalle and Koppo, 2021 ).…”
Section: Discussionsupporting
confidence: 54%
“…The above studies unfortunately lack data from other age groups. In human muscle, the CB1 protein levels seem to increase with age when compared between young (20–27 years) and old (≥65 years) individuals, and CB1 expression seems to increase with resistance exercise in older individuals [ 35 ]. Mice subjected to voluntary exercise for eight days exhibited increased eCB signaling in the Hip, accompanied by an increased progenitor cell proliferation within the DG.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that muscle type is an important determinant of CB 1 expression. Indeed, immunohistochemistry data from our lab showed that CB 1 expression was higher in slow human (MyHC + ) compared to fast human (MyHCI – ) muscle fibers (Dalle & Koppo, 2021). Unpublished data from our lab confirmed these findings in murine whole‐muscle tissue, as CB 1 protein expression was significantly higher in the slow m. Soleus compared to the faster m. Gastrocnemius and m. Quadriceps (Figure 5).…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%
“…Indeed, CB 1 gene expression was higher in the m. Gastrocnemius of 16‐month‐old compared to 4‐month‐old mice (Lipina et al, 2016). Accordingly, recent work indicated that CB 1 protein expression was significantly higher (~25%) in the m. Vastus Lateralis of old (65–84 years) compared to young adults (20–27 years) (Dalle & Koppo, 2021). However, Le Bacquer et al found CB 1 gene and protein expression to be lower in the m. Soleus , but not in the m. Extensor Digitorum Longus, of old (24 months) versus adult (6 months) rats (Le Bacquer, Salles, et al, 2021).…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%